Exploring Wellbeing and Creativity Through Collaborative Composition as Part of Hull 2017 City of Culture - Waddington-Jones, Caroline; King, Andrew; Burnard, Pamela (Frontiers in Psychology, 2019)
Several studies have highlighted the positive effects of group music-making and have suggested that it may be the creative and social aspects of such activities which have a positive effect on participants’ wellbeing. Collaborative composition offers strong examples of both aspects as participants work together to create new material. However, although it seems likely that participants’ influence over and ownership of the creative material contributes to these positive effects, studies have yet to examine these elements in detail. Through analysis of video observations, pre- and post-project interviews, video recall interviews, and questionnaires, this paper aims to: 1) evaluate the impact of participation in collaborative composition workshops on the subjective and psychological wellbeing of older adults; 2) identify skills and approaches employed by the composer-facilitators in order to understand more fully the approach and skills employed to engage participants effectively in the creative process. This second aim is of particular interest given the current movement towards social prescribing and arts and health interventions in the UK. Analysis revealed that all dimensions of the PERMA framework for subjective and psychological wellbeing (Seligman, 2010) were present in this collaborative composition project. The specific nature of collaborative composition is considered in comparison with other forms of group musical engagement. For older adults, collaborative composition has much to offer as an activity encouraging social interaction with others with shared interests, increasing positive affect, and enhancing self-esteem. Analysis of workshop videos and interviews with composers identified various facilitation skills employed by the composers to establish safe creative space and to encourage participants to engage in the process of collaborative composition.